The First World War and popular cinema : 1914 to the present - Paris, Michael, 1949- (Edinburgh University Press, 1999)
This text provides a comparative analysis of how the war has been remembered in film. It looks at how national cinemas were mobilised as part of the war effort and how, subsequently, film makers shaped the memory and legacy of the war in later years.